COVID-19 infection in an intensive care unit in Tunisia: Risk factors of mortality - Fatma Ben Youssef; Imene Mlouki; Oussama Jawed; Nihel Omri; Mohamed Fekih Hassen; Souheil ElAtrous; Habiba Ben SiK Ali; Sana El Mhamdi (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
Introduction: Identification of COVID-19 patients at high risk of mortality is crucial to improve patient management. Our study aimed to identify mortality risk factors at the COVID-19 Intensive Care Unit (ICU), in Mahdia. Methods: We conducted a prospective study including patients admitted to the COVID-19 ICU at University Hospital Tahar Sfar Mahdia (September 2020 to February 2021). We used "The RAPID CORE CASE REPORT FORM" developed by the World Health Organization. Results: A total of 119 patients were included (60.5% male). The average age was 61.9 ± 12 years. During their stay, 51.8% of them had invasive ventilation, 31.3 % required vasopressors intake and 50.9% required a prone position.  The mortality rate was 47.1%. Severe acute respiratory distress syndrome and Health Care Associated Infections (HAI) were associated with a higher risk of mortality (64.9% vs 17.8%; p < 0.001 and 81.1% vs 18.2 %; p < 0.001 respectively). Mortality was higher among intubated patients (79.7% vs 14.5%; p < 0.001). The mean Acute Physiology and Chronic Health Evaluation II (APACHII) score were higher in deaths than in survivors ((15.02 ± 7.6 vs 10.63 ± 5.31; p = 0.02). Low oxygen saturation on admission was associated with a higher risk of mortality (91.1% ± 6.44 vs 86% ± 11.25; p = 0.004).  Binary logistic regression showed increased odds of mortality with health-acquired infection (OR, 7.96 [95% CI, 2.28 - 27.7], severe acute respiratory distress syndrome (OR, 4.04 [95% CI, 1.11 - 14.73]) and invasive ventilation (OR, 12.23 [95% CI, 3.31 - 45.2]). Conclusion: Interventions preventing the risk factors are needed to improve the prognosis of Covid-19 patients.